Parasitic Fauna of Domestic Poultry in the Mountainous Regions of Armenia - R. E. Barseghyan; R. A. Petrosyan; L. J. Harutyunova; K. V. Akopyan; M. A. Nikoghosyan; N. E. Barseghyan; R. R.A. Jakmakian; N. N. Tadevosyan; Z. M. Dudukchyan; M. Z. Magomedova; P. D. Magomedova; M. V. Vardanyan (Юг России: экология, развитие)
The study aims to study the parasitic fauna of domestic poultry (chickens, turkeys, geese) in the mountainous zone of Armenia (Gegharkunik, Tavush regions).The material was collected from 2022 to 2023 in two regions of the mountainous zone of Armenia. A total of 107 samples of bird feces and 130 mollusks of the species Lymnaea stagnalis (Linnaeus, 1758) of the Lymnaeidae family – intermediate hosts of biohelminths – were examined. The study and species identification of parasites were carried out in the Laboratory of General Helminthology and Parasitology of the Scientific Center of Zoology and Hydroecology of the National Academy of Sciences of the Republic of Armenia. As a result of studying the species composition of the parasite fauna of domestic birds (chickens, turkeys, geese), their infection with helminths and protozoa, 3 species of nematodes (Ascaridia galli, Capillaria obsignata, Singamus trachea), 1 species of trematodes (Echinostoma revolutum) and 1 species of protozoa (Eimeria sp.) were identified. Mixed invasions (helminths + protozoa) were identified in all birds.The degree of invasion of helminths and protozoa varied. Eimeria were found in all examined birds with an extent of invasion from 36 % to 100 % and high rates of invasion intensity. The highest extent of helminthic invasion was recorded with Nematodosis and up to 86 % with Ascariasis with low rates of invasion intensity, which is apparently due to seasonal changes and zonal features of invasion, as well as timely implementation of therapeutic and preventive measures on farms.Timely detection and study of the spread of helminths in poultry and the diseases they cause is important for maintaining poultry health, productivity and high-quality production.